Hydrolysis of Mono-p-Toluidine Phosphate in Buffer Media - Awadhiya, Pragya; Bhoite, S.A. (Asian Journal of Chemistry, 2010)
Kinetic study of hydrolysis of mono-p-toluidine phosphate has been investigated in the pH range 0.00 to 7.46 at 50 ºC. The pH log rate profile has a rate maximum at pH 4.17. Hydrolysis of monoester carried out in buffer shows that only mononegative, mononegative and neutral species are reactive at pH 2.00-7.46 and pH 0.00 to 2.00, respectively. Their di-negative species have been found to be inert. The theoretical rate determined from specific rate and fractions of the neutral species agree closely with the experimental rates. The nature of molecularity of hydrolytic reaction has been decided on the basis of temperature and solvent effect. The monoester involves P-N bond fission, which is strengthened by comparative kinetic rate data.